(untitled) (The Journal of Psychology and Sociology, 2025)
The digital generation of students actively uses digital devices, virtually living in a digital environment and utilizing constantly updated app functionality, which impacts their mental health and well-being. The constant use of electronic communication devices and the internet creates both positive opportunities for personal development and has a potentially negative impact on students’ quality of life. The aim of this study was to diagnose problematic internet use in students and identify its impact on anxiety and self-esteem. The following diagnostic methods were used: the General Problematic Internet Use Scale, the Chen Internet Addiction Scale, the Weinhold Self-Esteem Questionnaire, and the Spielberger-Hanin Anxiety Scale. This article analyzes approaches to defining the concept of "problematic internet use" (PIU), distinguishing it from internet addiction, provides a review of research in Kazakhstan and internationally on the diagnosis and prevention of problematic internet use, and presents the results of an empirical study. The practical portion of the study involved 65 senior students (3rd and 4th years) at Al-Farabi Kazakh National University. The novelty and practical significance of the study stem from the identification of a significant correlation between problematic internet use and students’ anxiety and self-esteem. Recommendations for preventing problematic internet use are offered in conclusion. Keywords: internet addiction, problematic internet use, problematic mobile phone use, mental health, anxiety, self-esteem, diagnosis and prevention.